Perceptions of interdisciplinary education and readiness for inter-professional education of nursing students: A sample of three different cities in Turkey. (February 2021) - Köse Tosunöz, İpek; Karaçay Yıkar, Seda; Çerçer, Zehra; Kara, Pınar; Arslan, Sevban; Nazik, Evşen
Abstract: Background: In recent years, interprofessional education has been described as an opportunity for all healthcare professionals to enhance nursing quality by learning together and about one another. Determining perceptions and readiness of nurses regarding interprofessional education is important for effective education planning. Objectives: The aim of the study is to determine readiness for interprofessional learning and perceptions of interdisciplinary education of nursing students. Design: Descriptive and cross-sectional study. Settings: Nursing departments of public universities, in three different cities in Turkey. Methods: This study was conducted with 738 third- and fourth-year nursing students. The data of the study was collected using "Student Information Form", "Readiness for Inter-professional Learning Scale (RIPLS)", and "Interdisciplinary Education Perception Scale (IEPS)". The data was analyzed using descriptive statistics, Student's t -test, Kruskal-Wallis test, one-way analysis of variance (ANOVA), and correlation. Results: Mean age of the students was 21.56 ± 1.48, and the majority (72.9%) were women. Of the students, 58.9% chose their profession willingly, 56% chose the department as their first choice, 41.2% wanted to receive education with other healthcare students, and 84% reported having prior teamwork experience. Students' mean total scores of RIPLS and IEPS were respectively 69.78 ± 11.32 and 69.19 ± 16.62. There was a statistically significant difference between RIPLS mean scores and choosing the occupation willingly, order of choice, being satisfied with the choice of department, and willingness to study with other healthcare students, and between IEPS mean scores and choosing the occupation willingly, order of choice and being satisfied with the department choice (p < 0.05). Conclusion: Nursing students in three different cities had good readiness levels for interprofessional education and perception levels of interdisciplinary education, and differed according to certain demographical qualities. In addition, there was a positive relationship between readiness of inter-professional education, and perceptions of the students.